Theming Asia: culture, nature and heritage in a transforming environment. Issue 2 (15th March 2017) - Erb, Maribeth; Ong, Chin-Ee
ABSTRACT: This paper introduces a special issue on Theme Parks in Asia with reflections on how the various theoretical ideas on theming and theme parks that are found in the social science literature can help us to understand the proliferation of theming and theme parks in contemporary Asia. How does theming create a specific spatial and social form that has meaning in a transforming Asia? We trace here the rising importance of theming in places of consumption, education, entertainment and everyday life and argue that further attention is needed to understand the transformation of ideas of culture, nature and heritage within the context of theme park development in Asia. We look at arguments that suggest that theming is part of human cognitive processes, that it creates a frame that gives the content a particular order and meaning; we also consider theming within the context of theories of Disneyization and the 'experience economy' in leisure and tourism to explore how 'new' experience-based consumerism, and the designing of coherent 'imagineered' spaces, plays a role in ordering our social worlds. We also examine how debates over the authenticity or superficiality of theme parks, and more generally in cultural display and preservation, can take on new twists in Asia. We do this by drawing on a review of postmodernist perspectives on themed parks to show how theme parks in Asia can be better understood through nuanced inquiries into the ways cultural, natural and heritage images and icons are cited, referenced and projected, departing from a simple 'copy' versus 'original' dichotomy. Finally, we position and introduce the papers included in this special issue and suggest further possible research into such a fertile research field.